Pharmacological aspects of application of 1,2,4-triazole-3-thiol furan derivatives - O. A. Bihdan; V. V. Parchenko; О. І. Panasenko; E. G. Knysh (Zaporozhye State Medical University, 2016)
Introduction. Nowadays 1,2,4-triazole-3-thiol furan derivatives have established themselves as a separate class of promising bioactive compounds. Presented substance is practically non-toxic and exhibits various kinds of pharmacological activity. New original drug «Tryfuzol» in two dosage forms (1% injectable solution and 1% solution for oral administration) triumphantly entered the practice of the national veterinary. The most attractive in pharmacological aspects are water-soluble compounds 5-(furan-2-yl)-4R-1,2,4-triazole-3-thiols. Other classes of 1,2,4-triazole-3-thiol furan derivatives are also in considerable scientific interest. However, despite the presence of a sufficiently large number of publications, the issue of pharmacological tests systematization of the 1,2,4-triazole-3-thiol furan derivatives is still open. In this way the aim of our work was the systematization of the available sources of domestic authors. Materials and methods. Our work presents the results of systematic analysis of the available domestic literature related to the study of pharmacological properties of 1,2,4-triazole-3-thiol furan derivatives. Research results. It is known that 1,2,4-triazole-3-thiol furan derivatives have wide range of properties and biological activities. Thioacetate salts of corresponding acids show the highest results. The authors investigated the properties of water-soluble compounds of 1,2,4-triazole-3-thiol furan derivatives. Another group of compounds was investigated on hypoglycemic activity. It was established that the most active were piperidine 2-(5-(furan-2-yl)-4-(3-methylphenyl)-1,2,4-triazol-3-ylthio) acetate and piperidine 2-(5-(furan-2-yl)-4-phenyl-1,2,4-triazol-3-ylthio) acetate. Conclusion. The scientific potential of the domestic pharmaceutical industry has no doubts for today. The literature analysis of Russian authors proves the obvious prospect of further research of biologically active compounds among 1,2,4-triazole-3-thiol furan derivatives.